Ketertarikan Lalat Pada Fly Grill yang Berbeda Warna - Wulan Nugrahani; Avicena Sakufa Marsanti; Zaenal Abidin (Syntax Corporation Indonesia, 2022)
The objective of this research is to determine the difference between the yellow variations on the fly grill on the fly density. This study was carried out through pre-experimental research through a one-shot case study design. Furthermore, this research was conducted at Sambirejo Market, particularly the area that sells meat. In this case, there are 4 measurement points employed. The measurement of fly density was done for 30 seconds with 10 repetitions and each measurement average was determined. Furthermore, the data collected were analyzed using one-way ANOVA test and followed by an LSD test. Based on the research, results were obtained in the form that there was a significant difference between the fly grill and the yellow color variation on the fly density at Sambirejo market (p value = 0.035 < α = 0.05). In addition, there was also a significant difference between the dark yellow and golden fly grills (p value=0.007 < α = 0.05). In this case, the golden yellow fly grill is more effective in measuring the fly density than the dark yellow and light yello. It is further suggested that future researchers will use different bright colors and provide a grease on the surface of the fly grill using materials whose smell is preferred by fly such as meat or fish. Therefore, it will be more attractive for fly to perch.